Analysis of revision rhinoplasty; what is the problem and the management? - Alhadad, Mohamed; El Sakka, Dalia; Samy, Medhat; Fergany, Ahmed (International Surgery Journal, 2019)
Background: Revision rhinoplasty is reported to occur in 8% to 15%. Reoperation should be performed to correct deformities that were not diagnosed or addressed in previous surgeries, such as those from poor planning, performance and poor surgical healing. The aim of the study was to evaluate the problem of each case seeking revision rhinoplasty and different modalities for management to reach satisfactory results. Methods: This is a prospective study which was done in plastic surgery department, Menoufia University Hospitals over the period from December 2017 to December 2019. The study included 31 patients underwent previous rhinoplasty. Results: Patients were selected from the outpatient clinic, 31 patients who had varieties of nasal deformities. Mean age of the patients was 31.7 years. Female represent the majority of patients by 80.60% and males were 19.40% with significant difference in satisfaction (p=0.05). Patient satisfaction after surgery and it was excellent for 14 cases (45.20%), good for 9 cases (29 %) and it was fair in 8 cases (25.8%). Rhinoplasty outcome evaluation (ROE) score was correlated with patient satisfaction grades as mean of ROE score in excellent group was 67.5; in good group was 58.3; while in fair group was 38.8 with significant p value (0.001). Conclusions: Excellent patient satisfaction is related good planning, close follow up time, and less complication. Cartilage grafts especially rib cartilage is considered a lifeboat for revision rhinoplasty. We can link grades of patient satisfaction to ROE score.